Passive seismic localization without velocity model: application and uncertainty analysis - Khoshnavaz, Mohammad Javad; Chambers, K.; Bona, Andrej; Urosevic, Milovan (2015)
Passive seismic events are generally made by fault displacement, drilling, and hydraulic fracturing during high-pressure fluid injection into boreholes. There are two general configurations of seismic receiver arrays for passive seismic event monitoring: surface and down-hole. Surface arrays provide a larger aperture and hence greater coverage of the focal sphere in comparison to down-hole arrays. However, surface location techniques generally require knowledge of the velocity model to be known a priori. An alternative approach is passive seismic localization which is the procedure of identifying the focal point for the seismic wave field, which in many situations will coincide with the true source position. Whilst these procedures do require assumptions about the nature of the velocity model, it is not required to be parameterized a priori. In this paper, we propose a surface passive localization technique which is applied to both 2D synthetic and 3D field data examples. This work verifies that despite the approximations a reliable event location is achieved. The uncertainty of the proposed technique in the localization of passive seismic events using the bootstrap method was also studied.